Polyketide Derivatives in the Resistance of Gerbera hybrida to Powdery Mildew - Mascellani, Anna; Leiss, Kirsten; Bac-Molenaar, Johanna; Malanik, Milan; Marsik, Petr; Hernandez Olesinski, Estuardo; Tauchen, Jan; Kloucek, Pavel; Smejkal, Karel; Havlik, Jaroslav (Frontiers in Plant Science, 2022)
Powdery mildew is a common disease affecting the commercial production of gerbera flowers (Gerbera hybrida, Asteraceae). Some varieties show a certain degree of resistance to it. Our objective was to identify biomarkers of resistance to powdery mildew using an 1H nuclear magnetic resonance spectroscopy and chemometrics approach in a complex, fully factorial experiment to suggest a target for selection and breeding. Resistant varieties were found to differ from those that were susceptible in the metabolites of the polyketide pathway, such as gerberin, parasorboside, and gerberinside. A new compound probably involved in resistance, 5-hydroxyhexanoic acid 3-O-β-D-glucoside, was described for the first time. A decision tree model was built to distinguish resistant varieties, with an accuracy of 57.7%, sensitivity of 72%, and specificity of 44.44% in an independent test. Our results suggest the mechanism of resistance to powdery mildew in gerbera and provide a potential tool for resistance screening in breeding programs.